Eco Architecture on Design Creative Center for Children in Medan - Sonia Sabira Lubis; Nelson M. Siahaan (Talenta Publisher, 2019)
Childhood is one phase of human that plays an important role for children, especially of the child’s brain. Besides that, generals in this phase, the creativity and the character development of children also begin to form. Indonesia has diverse cultures, religions, and languages. Traditional games are also included in cultural diversity. But unfortunately, as the development of science and technology progresses like digital games, these games have gradually begun to extinct and is rarely played by children. The project tries to overcome the problem by designing a building that can become an educational and recreation area. The methodology of this project starts from conducting site selection by literature studies, then the design problem-solving phase, namely by searching ideas, collecting data, literature studies, observation studies, comparative studies. This research produces buildings that can respond to these problems by applying the concepts of ecology architecture to the design. The benefit of this design is that children are more familiar with traditional games and energy-efficient buildings.